Technology Platforms as an Efficient Tool to Modernize Russia’s Economy - Galimulina, Farida F.; Shinkevich, Alexey I.; Komissarova, Irina P.; Mayorova, Albina N.; Astafyeva, Irina A.; Klimova, Natalia V.; Nabiullina, Karina R.; Zhukovskaya, Irina V. (International Journal of Economics and Financial Issues, 2016)
There is an urgent need to consider the dynamic development of the global economy from the point of view of its positive impact on competitiveness improvement in national manufacturing industries, and the best ways to modernize the country economy. The purpose of the paper is to provide with perspectives for development of instruments related to technology platforms within the framework of innovation management and adapted to the conditions of Russia’s economic reality. The major method in studying this issue is mathematical economic modeling which has made it possible to facilitate expediency in determining a technology platform as an effective innovation control instrument. The paper considers European and Russian experience in deploying technology platforms, and identifies national features characteristic to the performance of the innovation management instrument. A mathematical economic model is used for justifying the efficiency of introducing technology platforms into Russian institutional innovation system. The practical significance of results and conclusions is in its ability to improve the mechanisms of developing and implementing federal and regional innovation development programs, development of the innovation infrastructure, stimulation of the innovation activity, use of a set of technology platform instruments by public authorities. Keywords: technology platforms, innovative development, modernization, triple helix. JEL Classifications: C02, C18, O21